2002
DOI: 10.1109/72.977314
|View full text |Cite
|
Sign up to set email alerts
|

ViSOM - a novel method for multivariate data projection and structure visualization

Abstract: Abstract-When used for visualization of high-dimensional data, the self-organizing map (SOM) requires a coloring scheme such as the U-matrix to mark the distances between neurons. Even so, the structures of the data clusters may not be apparent and their shapes are often distorted. In this paper, a visualization-induced SOM (ViSOM) is proposed to overcome these shortcomings. The algorithm constrains and regularizes the inter-neuron distance with a parameter that controls the resolution of the map. The mapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, it is difficult to visualize class boundaries in self-organizing maps. As discussed in Section 1 , there have been many attempts to visualize connection weights [ 3 , 6 , 8 , 14 , 16 , 17 , 26 – 28 ]. One of the main problems lies in the focus upon cooperation between neurons in the conventional self-organizing maps; neighboring neurons must behave as similarly as possible.…”
Section: Theory and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to visualize class boundaries in self-organizing maps. As discussed in Section 1 , there have been many attempts to visualize connection weights [ 3 , 6 , 8 , 14 , 16 , 17 , 26 – 28 ]. One of the main problems lies in the focus upon cooperation between neurons in the conventional self-organizing maps; neighboring neurons must behave as similarly as possible.…”
Section: Theory and Computational Methodsmentioning
confidence: 99%
“…While the above techniques are applied to SOM results, there are several methods where connection weights are actively modified so as to improve class structure. For example, the visualization induced self-organizing map (ViSOM) [ 14 ] was introduced to preserve data structure and topology as faithfully as possible by regularizing the distances of interneurons. Along the same line, the probabilistic regularized self-organizing map (PRSOM) [ 15 ] was also proposed to regularize interneuron distances by introducing the MDS type metric to preserve pair-wise distances between neurons in the input and output space.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in [16] the inter-point distances in the feature space between the SOM neurons are used for presenting graphically the underlying structure of the data. A further refinement of these approaches is the visualization-induced SOM [29] an algorithm that regularizes and scales the inter-neuron distances so as to control the resolution of the mappings.…”
Section: Introductionmentioning
confidence: 99%
“…These include sizes of the receptive fields, local density distribution or distance (or similarity) across node prototypes. These components have been exploited for visualization of data clusters via several visualization schemes such as U-matrix [27] or its variants [28], [29], visualization-induced SOM [30], or double SOM [31]. A more comprehensive review on various visualization schemes of the SOM can be found in [26], [32], and [33].…”
Section: Introductionmentioning
confidence: 99%